Characterization of a cryptic gene pair from Neisseria gonorrhoeae that is common to pathogenic Neisseria species. - Seifert, H S (1992)
A pair of genes, each of which produces in Escherichia coli a 20-kDa, periplasmically localized protein that cross-reacts with anti-rpoN monoclonal antibody, was isolated from Neisseria gonorrhoeae. Homologs of the two genes were detected in pathogenic Neisseria species but not in commensal species. These genes are designated cnp1 and cnp2 (cryptic neisserial protein).